2022
DOI: 10.1111/tbed.14483
|View full text |Cite
|
Sign up to set email alerts
|

Live pig markets are hotspots for spread of African swine fever virus in Nigeria

Abstract: Livestock trading through live animal markets are potential pathways for the introduction and spread of economically important pathogens like the African swine fever virus (ASFV) to new areas in several countries. Due to the high demand for live pigs in Nigeria both for restocking and slaughter, live pigs are sold at designated live pig markets (LPM) in the country. This involves movement of pigs over long distances. Despite, reports of ASF outbreaks following restocking of pigs bought from LPMs, there is pauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…This would be impractical for smallholder farmers, and in small premises with limited resources, effective quarantine is usually not an option [ 64 ]. Safe sources of new pigs might be difficult to find, with live markets and itinerant pig traders considered as posing a high risk [ 29 , 103 ]. It has been suggested that quarantine at community level may be possible in smallholder settings, for example, in a village if facilitated by the village head [ 13 ].…”
Section: Mitigating Well-documented Risksmentioning
confidence: 99%
See 3 more Smart Citations
“…This would be impractical for smallholder farmers, and in small premises with limited resources, effective quarantine is usually not an option [ 64 ]. Safe sources of new pigs might be difficult to find, with live markets and itinerant pig traders considered as posing a high risk [ 29 , 103 ]. It has been suggested that quarantine at community level may be possible in smallholder settings, for example, in a village if facilitated by the village head [ 13 ].…”
Section: Mitigating Well-documented Risksmentioning
confidence: 99%
“…Live markets where pigs are sold are common in many countries. The risk of ASF is increased when pigs from different sources are assembled [ 29 , 103 , 106 , 142 , 160 ]. The source of outbreaks outside the ASF-controlled area in South Africa in 2012 was a facility where live pigs were sold by auction [ 161 ] and infection was detected in a proportion of pigs sampled at four live markets in Nigeria [ 29 ].…”
Section: Mitigating Well-documented Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the potential for ASF to survive on contaminated surfaces, such as transportation vehicles, for several days could lead to transmission via indirect contact (Y. Li et al, 2020; Yoo et al, 2021; Adedeji et al, 2022; Galli et al, 2022), another important route in ASF dissemination (Kim et al, 2021; Yoo et al, 2021; Cheng and Ward, 2022; Galli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%